New Voices. Issue 1 (31st December 2023) - Whitman, Laura; Weinstein, Lissa
ABSTRACT: New Voices is a section with psychoanalytically informed writing by students at the college, graduate, and post-graduate level. Papers may concern psychoanalytic ideas as they are relevant to clinical dilemmas, educational experiences, or culture, including literature, film, music, and socio-political issues. Submissions would ideally provide information on what areas are of most interest to younger colleagues. The encouragement of psychoanalytic writing at an early level could create a connection between university and residency programs and the world of psychoanalytic thought.